2020
DOI: 10.1101/2020.04.04.024562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZNF423patient variants, truncations, and in-frame deletions in mice define an allele-dependent range of midline brain abnormalities

Abstract: Interpreting rare variants remains a challenge in personal genomics, especially for disorders with several causal genes and for genes that cause multiple disorders.ZNF423 encodes a transcriptional regulatory protein that intersects several developmental pathways. ZNF423 has been implicated in rare neurodevelopmental disorders, consistent with midline brain defects in Zfp423-mutant mice, but pathogenic potential of most patient variants remains uncertain. We engineered ~50 patient-derived and small deletion var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
2
1
Order By: Relevance
“…Both survival and behavioral ataxia were substantially more penetrant on B6 than BALB, although statistical support for anatomical differences were sub-threshold and likely underpowered relative to the observed variance. This strain difference in sensitivity contrasts with recent work in our lab comparing different alleles on a single inbred background, where anatomical differences were more sensitive than behavior in a more extensive series of animals [17]. Surviving Zfp423 nur12 mutants from intercross and backcross designs reported here showed that no single locus is either necessary or sufficient for mutant survival, but taken together, our results supported the existence of a modifier locus on chromosome 5, with suggestive or significant support for linkage at other loci being cross-dependent.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Both survival and behavioral ataxia were substantially more penetrant on B6 than BALB, although statistical support for anatomical differences were sub-threshold and likely underpowered relative to the observed variance. This strain difference in sensitivity contrasts with recent work in our lab comparing different alleles on a single inbred background, where anatomical differences were more sensitive than behavior in a more extensive series of animals [17]. Surviving Zfp423 nur12 mutants from intercross and backcross designs reported here showed that no single locus is either necessary or sufficient for mutant survival, but taken together, our results supported the existence of a modifier locus on chromosome 5, with suggestive or significant support for linkage at other loci being cross-dependent.…”
Section: Discussioncontrasting
confidence: 91%
“…This suggests that searches for survival loci might be more powerful in strains with low survival frequency and close relation to B6, as these should limit the number of contributing loci and therefore the statistical power per surviving mutant. These results also informed our choice of strains for modeling patient variants of uncertain significance [17], where FVB provided a high-survival, yet fullypenetrant background compatible with recovery of severe alleles and B6 provided a sensitized background to increase confidence in negative findings [17].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation